Antibacterial activities and molecular identification of endophytic fungi isolated from mangrove Avicennia marina - YENI MULYANI; ASRI PENI WULANDARI; SISKA ELISAHBET SINAGA; WAHYU SAFRIANSYAH; AZMI AZHARI; SARI PURBAYA; FAJAR FAUZI ABDULLAH; KINDI FARABI; YOSHIHITO SHIONO; UNANG SUPRATMAN (Society for Indonesian Biodiversity, 2023)
Abstract. Mulyani Y, Wulandari AP, Sinaga SE, Safriansyah W, Azhari A, Purbaya S, Abdullah FF, Farabi K, Shiono Y, Supratman U. 2023. Antibacterial activities and molecular identification of endophytic fungi isolated from mangrove Avicennia marina. Biodiversitas 24: 6923-6933. This research explored the antibacterial potential of endophytic fungi from the Avicennia marina's (Forssk.) Vierh leaves, stem bark, and root, located in Blanakan, Subang District, West Java. The screening process for antibacterial activity potential was conducted using the Kirby Bauer disk diffusion method. Subsequently, the molecular screening results of the most promising fungi species were identified using Internal Transcribed Spacer (ITS) markers. The results revealed the isolation of 30 fungal isolates. Among these, seven endophytic fungi exhibited significant antibacterial activity against Staphylococcus aureus ATCC 29213 and Vibrio harveyi ATCC 5339, with inhibition zones ranging from 7.88±1.52 to 23.60±0.77 mm. Through molecular identification, 7 endophytic fungi were identified, including Penicillium chrysogenum, Cladosporium anthropophilum, Trichosporon asahii, Cladosporium sphaerospermum, Fusarium verticillioides, Meyerozyma carpophila, and Penicillium steckii. Notably, C. anthropophilum exhibited the highest inhibition zones against S. aureus and V. harveyi measuring 23.60±0.77 and 21.80±0.26 mm, and showed (Minimum Inhibitory Concentration) MIC values of 15.625±0.98 and 31.25±0.39 ?g/mL, respectively. In this study, endophytic fungi isolated from different parts of A. marina exhibited promising antibacterial activity, with Cladosporium anthropophilum from the stem bark showing the highest potency against S. aureus and V. harveyi, suggesting their potential as a source of antibacterial agents. To the best of our knowledge, this is the inaugural study uncovering the isolation and antibacterial potential of endophytic fungi from the genera Cladosporium, Trichosporon, Fusarium, and Meyerozyma. These fungi were extracted from the bark, leaves, and roots of A. marina, situated within the unique mangrove ecosystem of Blanakan Sub-district, Subang District, West Java, Indonesia.